Reset redux: possible evolutionary pathways towards the transformation of tourism in a COVID-19 world. Issue 3 (26th May 2020) - Brouder, Patrick
Abstract: With international arrivals surpassing 1.5 billion for the first time in 2019 the long-term evolution of tourism demonstrates prolific path dependence with a decade of growth since the global financial crisis. This latest period of unfettered international tourism development has come to an abrupt end as the impact of COVID-19 has brought the sector to a near standstill. As the world grapples with the realities of the global pandemic there is an opportunity to rethink exactly what tourism will look like for the decades ahead. Key concepts in evolutionary economic geography, especially path dependence/creation and institutional inertia/innovation, show variations in pathways for travel and tourism in a COVID-19 world. A path that leads to transformation in tourism can be realized if sufficient institutional innovation occurs on both the demand and supply side of tourism that can foster the emergence of new paths. COVID-19 presents a once in a generation opportunity where the institutional pump is primed for transformation. Whether that leads to a radical transformation of the tourism sector remains to be seen, but the imprint it will leave on both the demand and supply of tourism will have long-term, incremental impacts for years to come and ultimately move us closer towards the transformation of tourism.